Investigation of methylation CpG islands in p16 and p15 genes in cutenaous and uveal malignant melanoma - Mackiewicz, Andrzej; Kwiatkowska, Eliza; Gmyrek, Grzegorz; M. Lamperska, Katarzyna (Contemporary Oncology/Współczesna Onkologia, 2001)
Changes in the chromosome region 9p21 in many types of tumors including malignant melanoma were observed. There are two suppressor genes in this region: p16 (CDKN2A) and p15 (CDKN2B). Number of mechanism might be involved in inactivation of these gens. They include: homozygous and heterozygous deletions, point mutations and methylation of the promoters. In the Department of Cancer Immunology we investigated 110 cases of cutenaous and uveal malignant melanoma. We found no methylation in CpG islands in promotor regions of p16 and p15 genes. It seems that methylaton of promoters is not responsible for inactivation of both genes in cutenaous and uveal malignant melanoma.